Philosophy Studies in Elementary Schools - Helda Kusuma Wardani (Berpusi Publishing, 2024)
When a teacher thinks about why an educational act is done? The answer to that question will boil down to the beginning of the process of the education system. The beginning and estuary of the process of the education system are deep-rooted ideas about education itself which are often referred to as educational philosophy. The need for the study of educational philosophy is urgent to help every Elementary School ( ES ) teacher realize the importance of answering the question